The Utilization of a Combination of Heatsink Material And A Water Cooler Block As An Effort To Reduce Heat From Solar Panels - Abdullah; Putri, Maharani; Syahruddin, M.; Silitonga, Arridina Susan; Dharma, Surya; Jumaat, Abdul Kadir; Ridzuan, Abdul Rahim; Aritonang, Gideon (MultiTech Publisher, 2024)
Solar panels are an important utilization in generating renewable energy, but high temperatures can reduce energy conversion efficiency and shorten the lifetime of solar panels. This research aims to explore and evaluate the utilization of a combination of heatsink material and cooling water block as a solution to reduce the heat generated by solar panels. The research method includes the design and manufacture of a prototype consisting of solar panels mounted on a combination of heatsink material and water block. Experiments were conducted by varying the use of passive cooling and the absence of cooling on solar panels according to environmental conditions to evaluate the effectiveness of the system in reducing the temperature of solar panels. A power increase of 43.3% was achieved by comparing the system without cooling design with the passive cooling design system. The results showed that the use of a combination of heatsink material and cooling water block significantly reduced the solar panel temperature under various operational conditions. In addition, data analysis showed an increase in the energy conversion efficiency of the solar panel after the implementation of the cooling system. This research makes an important contribution to the development of more efficient and durable solar panel technology by addressing the problem of heat generation.